Commuter Students and Psychological Sense of Community: How Ties to Home Relate to Academic Success - Smith Brian T.; Charlton Kelly; Allen Ashley Batts (De Gruyter, 2023)
Universities spend significant time and energy establishing a sense of community for their students. University personnel strive to increase school community ties for commuter students who travel back and forth from home to campus under the assumption that these increased ties will predict academic success. In an effort to understand those variables related to commuter student success, 335 participants responded to questions regarding commuter status, psychological sense of community with one's school, psychological sense of community with one's hometown, and academic self-handicapping. Results indicated that those with a strong sense of community with their hometown were less likely to engage in academic self-handicapping. Moreover, this relationship was moderated by commuting status, such that the effect was stronger for commuter students than for non-commuter students. Implications for commuter student success and future research are discussed.